Cervical Spine Ischemic Stroke Complicated by Spastic Quadriparesis and Ogilvie Syndrome: A Case Report and Literature Review. (15th July 2020) - Assad, Salman; Nolte, Justin; Singh, Dharampreet; Hanif, Samrina; Ferguson, Paul
Abstract : Infarction or ischemia of the spinal cord is a rare entity and is often misdiagnosed as inflammatory myelopathy in acute settings. Atherosclerotic disease can affect spinal arteries, leading to cord ischemia with clinical presentation mixed with myelopathy. We present a case of a 66-year-old male who came to the hospital with unsteady gait and numbness of all extremities without associated pain for the past 48 hours. The neurological examination on admission directed the diagnosis towards myelopathy of the cervical spine. However, the initial magnetic resonance imaging (MRI) of the cervical spine demonstrated gliosis and restricted diffusion of the cord with multilevel neuroforaminal stenosis but without central canal stenosis or cord compression. The MRI brain, cerebrospinal fluid analysis, and rheumatologic evaluation were unremarkable. Four days into the clinical course, the patient developed weakness and spasticity of all extremities prompting further evaluation. Computed tomography angiography (CTA) scan of the head and neck revealed right vertebral artery occlusion and intracranial atherosclerotic disease. He was started on aspirin and clopidogrel for secondary risk reduction. The hospital course was further complicated by Ogilvie syndrome (OS), and the patient underwent uncomplicated cecostomy.